Multi-Criteria Decision Analysis of the Environmental and Economic Parameters for Mineral Carbonation of Steel Slags as a Carbon Capture, Utilization and Storage Materi - Ponnapat Watjanatepin; Laura Steinwidder; Anthony de Schutter; Nina Miladinović; Tom Van Duyse; Lola Eelen; Giuseppe Granata; Sara Vicca; Tom Van Gerven; Karel Van Acker (Journal of Sustainable Development of Energy, Water and Environment Systems, 2025)

(untitled)
Mineral carbonation, where steel slags react with carbon dioxide from flue gases to form stable carbonates and silicates, offers a potential carbon capture, utilization, and storage pathway with agricultural applications. However, it is essential to assess the environmental and economic impacts to determine its industrial feasibility. The trade-offs between the environmental and economic impacts would provide the most optimal scenario for further upscaling and adoption of mineral carbonation of steel slags as a carbon capture, utilization and storage technology. This study quantifies the environmental and economic impacts of steel slag mineral carbonation, using life cycle assessment and life cycle costing respectively, and identifies optimal trade-offs using multi-criteria decision analysis. Basic oxygen slags with treatment 2 was identified as the optimal condition, based on the weighting of equal environmental and economic importance, for further optimization and scaling of the mineral carbonation process. In conclusion, these findings contribute to advancing steel slag mineral carbonation and enhancing the sustainability of the steel manufacturing value chain.